Environmental Epigenetics - Su, L. Joseph (Springer, 2015)
Human population is simultaneously and continuously exposed to a wide variety of chemical substances, biological agents, physical agents, and other stressors in daily life. The exposures can modify health consequences or potentiate the response expected from the exposure. Over the past decades, it has been a raised awareness of the environmental pollution to the health of human. Despite the effort of remedia tion and better control of the pollution, many of nature disasters, such as oil spill in the Gulf of Mexico, Fukushima nuclear plant disaster in Japan, and levee failure in New Orleans after Hurricane Katrina, or manmade products, such as bisphenol-A in food containers and a widely used plasticizer, di(2-ethylhexyl) phthalate (DEHP), presence of fungicides, vinclozolin and prochloraz, in foods, inappropriate disposal of electronic boards that contain heavy metals, and pharmaceutical use of finaste ride, continuously pose threat to the human health...